2018
DOI: 10.1002/ccd.28037
|View full text |Cite
|
Sign up to set email alerts
|

Optimal medical therapy vs. coronary revascularization for patients presenting with chronic total occlusion: A meta‐analysis of randomized controlled trials and propensity score adjusted studies

Abstract: Introduction:The optimal management of patients with coronary chronic total occlusions (CTO) remains controversial. This meta-analysis aims to compare percutaneous coronary intervention of CTO (CTO-PCI) versus optimal medical therapy (OMT) in CTO patients.Methods: A literature search with highly specific terms was conducted using MEDLINE, EMBASE, and Web of Science to identify most relevant randomized controlled trials (RCTs) and observational studies with propensity score matching (PSM) evaluating differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
(49 reference statements)
0
13
0
1
Order By: Relevance
“…Additionally, the incidence of MACE-although defined differently in the studies-did not differ significantly at several time points during follow-up. This was also demonstrated in a previous meta-analysis by Iannaccone et al [21], but observational studies were also included which could have distorted the results. It is noteworthy that both mortality rate and MACE incidence are low, even after 4 years of follow-up.…”
Section: Clinical Endpointsmentioning
confidence: 66%
“…Additionally, the incidence of MACE-although defined differently in the studies-did not differ significantly at several time points during follow-up. This was also demonstrated in a previous meta-analysis by Iannaccone et al [21], but observational studies were also included which could have distorted the results. It is noteworthy that both mortality rate and MACE incidence are low, even after 4 years of follow-up.…”
Section: Clinical Endpointsmentioning
confidence: 66%
“…Por último, en un metanálisis se estudiaron los 4 ensayos aleatorizados descritos previamente y 3 estudios observacionales, y no se encontraron diferencias en el objetivo compuesto primario analizado (muerte cardiovascular, infarto de miocardio y reintervención coronaria). El análisis independiente de cada uno de los componentes observó que el intervencionismo tuvo un mejor resultado en cuanto a muerte cardiovascular (OR = 0,52; IC95%, 0,33-0,81; p < 0,01), fundamentalmente a expensas de los resultados favorables en los estudios observacionales 26 .…”
Section: Estudios Observacionalesunclassified
“…Previous meta-analyses on the present context were restricted to studies with propensity-matched analysis and only reported the pooled hazard ratio and often did not separately report outcomes of PCI and coronary artery bypass grafting (CABG) in comparison to OMT. 8 , 9 , 10 To overcome the lacunae of evidence, we reported the first meta-analysis incorporating both randomized and observational studies. 11 The aim of the present study was to conduct a meta-analysis of published data of observational as well as randomized studies comparing long term outcomes of PCI with OMT versus OMT alone in patients with CTO ( Online supplemental material, Supplement 1, PICO strategy ).…”
Section: Introductionmentioning
confidence: 99%